Monumen Sebagai Media Pendidikan Sejarah di Desa Bahu Palawa Kalimantan Tengah - Tigoi, Alesandro Mikhael; Reynaldie, Kevin; Shahada, Muhammad Azhar; Mirozea, Yudha Fernandho; Angelina, Stephanie; Valentina, Sesilia; Sustari, Izabel Putri Devi; Gawei, Apria Brita Pandohop (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
Community Service Program focus on the Independent Campus Learning KKN Community Service Program is a community service program initiated by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. This program is expected to train students' creativity in designing ideas that are relevant to local needs, develop solution-oriented thinking skills, and encourage active community participation in the design process. The objective of the 2024 Field Study Program is to design a monument based on local wisdom, which not only has aesthetic and symbolic functions but is also expected to have a social, cultural, and economic impact on the surrounding community. The main program of designing the monument is an implementation planned by the village apparatus who want to   develop Bahu Palawa village as a tourist village that is expected to be a reminder of history, but also a representation of togetherness and a means of community empowerment. The monument design method and site plan were carried out through field observation, collection of social and cultural data on the community, and design using SketchUP and AutoCAD software as well as 3D structural modeling in Autodesk Revit. The results of the Community Service Program were the planning of the monument structure and the design of the monument as a tourism facility that can help generate income for the welfare of the village and the community of Bahu Palawa Village, Kahayan Tengah District, Pulang Pisau Regency